How Can the Use of Authentic Materials Foster Second Graders’ Communicative Competence in an EFL Course at a Public Elementary School? (2019)
ABSTRACT: This action research was intended to foster second graders’ communicative competence using authentic materials in an EFL context at a public school in Itagüí. Data were collected through a journal, oral presentations, listening activities, and an interview to the teacher. Data analysis revealed that the use of authentic materials had a positive impact on students’ communicative competence as there was significant improvement of students’ oral production and listening comprehension. Additionally, the exposure to the second language positively influenced the students’ confidence to use English in the classroom and increased their motivation. However, some limitations such as time constraints and lack of materials had some negative influence on the results. It would be interesting to explore the benefits of authentic materials in other EFL contexts.